# Answers and Solutions

Question:

Please solve the equation.

3px-py+3qx-qy

Posted by: Ujjwal on 19.08.2022

Answer:   An equation should have  one LHS and one RHS with an equal sign between them.

If the eqauality sign doesnt exist, then it is not an equation ,but only an expression.An expression could only be simplified and cannot be solved as there is nothing to solve. The present question is only an expression and so cannot be solved.The students should clearly understand the difference between expression and equation.

Its not an equation but an expression. See attachment
3px-py+3qx-qy Take 3x common from 1st and 3rd term 3x(p+y)-py-qy Now take -y common 3x(p+q)-y(p+q) Now take p+q common (p+q)(3x-y)

3px-py+3qx-qy

=p(3x-y)+q(3x-y)

=(p+q)(3x-y)

(3x-y)(p+q)

=3px-py+3qx-qy

=3x(p+q)-y(p+q)

=(p+q)(3x-y)

3px-py+3qx-qy=3px+3qx-py-qy=3x(p+q)-y(p+q)=(p+q)(3x-y)

3px - py + 3qx - qy

= p (3x-y) + q (3x-y)

= (3x-y) (p+q)

### Post Answer and Earn Credit Points

Get 5 credit points for each correct answer. The best one gets 25 in all.

Similar Questions
Topic Cloud

## Need a Tutor or Coaching Class?

Post an enquiry and get instant responses from qualified and experienced tutors.

Post Requirement